(3JYdjb Ydi cJGH GQTejOS aj GdGSWhGfg hGdcQI hJMQjQgs - (3GQTejOSs
(3ChdgG (B:s
(3HYO GdHSedI Gbhd HYO JMejO Gddg hJeLjOI Gfj cfJ aj WdH GdhbhaI Ydi HYV GdeSGFd GdePchQ aj cJGH GdcQI hGdGSWhGfI dCQTejOS s
(3BNQgG (B:s
(3hjchf CMOgeG GbQH Edi GdfUa ef GdGNQj hPdc eG GQOfGg agPG eG GhQOg GHh Sgd s
(3Vef eLehY , JQJjHgG (B: 13s
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
(3chHQjdj (B(1930) s
Keywords: (3eJaQbGJs